Channelpedia: An Integrative and Interactive Database for Ion Channels - Ranjan, Rajnish; Khazen, Georges; Gambazzi, Luca; Ramaswamy, Srikanth; Hill, Sean L.; Schürmann, Felix; Markram, Henry (Frontiers in Neuroinformatics, 2011)
Ion channels are membrane proteins that selectively conduct ions across the cell membrane. The flux of ions through ion channels drives electrical and biochemical processes in cells and plays a critical role in shaping the electrical properties of neurons. During the past three decades,extensive research has been carried out to characterize the molecular, structural and biophysical properties of ion channels. This research has begun to elucidate the role of ion channels in neuronal function and has subsequently led to the development of computational models of ion channel function. Although there have been substantial efforts to consolidate these findings into easily accessible and coherent online resources, a single comprehensive resource is still lacking. The success of these initiatives has been hindered by the sheer diversity of approaches and the variety in data formats. Here, we present “Channelpedia” (http://www.Channelpedia.net) which is designed to store information related to ion channels and models and is characterized by an efficient information management framework. Composed of a combination of a database and a wiki like discussion platform Channelpedia allows researchers to collaborate and synthesize ion channel information from literature. Equipped to automatically update references, Channelpedia integrates and highlights recent publications with relevant information in the database. It is web based, freely accessible and currently contains 187 annotated ion channels with 45 Hodgkin-Huxley models.